PREVENTION OF MASS VIOLENCE BY POLRI IN THE PROFETIC LAW PERSPECTIVE - Purwadi W Anggoro (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain prophetic concept of preventing the occurrence of criminal acts that cause casualties in mass violence that can be carried out by the National Police. The results of the study that Polri is a state tool that has the task of providing protection, protection and service to the community while at the same time having authority as a law enforcer. The National Police has the duty to prevent activities that can lead to conflict and can disrupt public order and even state security, as an example of efforts that have been made, namely by providing humanitarian services in the form of security measures for participants of the 212 demonstrations by taking preventive approaches. The National Police gave a religious psychology touch to the participants of the demonstration to be orderly and orderly while at the same time providing understanding to the demonstrators that disorder, slander, violence and even riots were sins and actions that were forbidden by Islam and Allah SWT. The Polri's efforts are to restore human nature, cleanse themselves and restore the awareness that brotherly relations and amar ma'ruf nahi munkar are gifts from Allah SWT that need to be guarded and accounted.